The preparation and characteristics of chicken feather / epoxy composites / Ahmad Zafir - Zafir, Ahmad (Institute of Graduate Studies, UiTM, 2012)
The uses of the natural fibre in the fabrication of the composites are being studied all over the world. Most of the fibre used comes from trees. In this research, the fibre or filler used is obtained from chicken feather. The chicken feather was washed and pulverised to obtain a shorter and uniform fibre. Few tests were carried out as to ensure the processed chicken feather will not degrade due to the washing and drying.